2022
DOI: 10.3390/medicina58080993
|View full text |Cite
|
Sign up to set email alerts
|

Rosinidin Protects Streptozotocin-Induced Memory Impairment-Activated Neurotoxicity by Suppressing Oxidative Stress and Inflammatory Mediators in Rats

Abstract: Background and Objectives: To assess the antioxidant and neuroprotective role of rosinidin on rat memory impairment that is induced by streptozotocin. Materials and Methods: Wistar rats were given an intraperitoneal (i.p) injection of streptozotocin (60 mg/kg) followed by treatment with rosinidin at selective doses (10 and 20 mg/kg) for 30 days. The behavioral parameters were estimated by Y-maze test and Morris water test. Biochemical parameters such as acetylcholinesterase (AChE), choline aacetyltransferase (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Acetylcholine (ACh) plays a significant role in cholinergic neuron functioning in the hippocampus and controls the learning and memory process [ 63 ]. In the cholinergic system, choline acetyltransferase (ChAT) and AChE are involved in the synthesis and metabolism of ACh, respectively; however, STZ administration increases AChE activity [ 64 ]. The increased AChE activity leads to decreased ACh concentration that affects cognitive functioning [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acetylcholine (ACh) plays a significant role in cholinergic neuron functioning in the hippocampus and controls the learning and memory process [ 63 ]. In the cholinergic system, choline acetyltransferase (ChAT) and AChE are involved in the synthesis and metabolism of ACh, respectively; however, STZ administration increases AChE activity [ 64 ]. The increased AChE activity leads to decreased ACh concentration that affects cognitive functioning [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…To assess the spatial cognitive ability of mice, the MWM test was performed in the eighth week, and the whole water maze test includes positioning navigation trail and spatial probe test. 23,24 In the positioning navigation trail, mice were put into the water facing the wall of the pool at a regular time period every day, and the time it takes to search for and climb onto a platform was recorded as the escape latency. Each mouse received daily training from four different quadrants for five consecutive days.…”
Section: Morris Water Maze (Mwm) Testmentioning
confidence: 99%
“…In the future, biomarkers should be available not only for early diagnosis, but also for indicating responses to specific therapeutic interventions that help to guide treatment decisionsfor AD. Alharbi et al [ 6 ] demonstrated the anti-inflammatory and anti-oxidant action of rosinidin in streptozotocin-induced rats, improving their cognitive and spatial learning behavior. These are promising results and suggest rosinidinas a therapeutical agent for further neurodegenerative disorder-related clinical trials.…”
mentioning
confidence: 99%